High voltage electrochemical exfoliation of graphite for high-yield graphene production. Issue 50 (17th September 2019) - Roscher, Sarah; Hoffmann, René; Prescher, Mario; Knittel, Peter; Ambacher, Oliver
Abstract : We demonstrate a highly efficient, single-step, cathodic exfoliation process of graphite to produce single- to few-layer graphene with a yield of over 70% from natural graphite flakes. Abstract : We demonstrate a highly efficient, single-step, cathodic exfoliation process of graphite to produce single- to few-layer graphene with a yield of over 70% from natural graphite flakes. By employing boron-doped diamond electrodes high potentials up to −60 V can be applied which was found to greatly increase the yield. The produced graphene flakes are partially hydrogenated during the electrochemical treatment likely aiding in their exfoliation. The resulting flakes have a large lateral size with up to 50 μm diameter. Due to the reversibility of the hydrogenation by thermal treatment the graphene flakes possess a low defect density as judged by the Raman D/G ratio yielding highly conductive films with sheet resistances of 100 to 3200 Ω □ −1 at 10 to 70% transparency.